MEREKONSTRUKSI MODEL KEPEMIMPINAN TRIPLE HELIX DALAM IMPLEMENTASI PEMBERDAYAAN MASYARAKAT DI ERA OTONOMI - Alimas Jonsa (Universitas Teuku Umar, 2015)
With Reconstructed of leadership model in triple helix implementation become the most important with the context of integrated nationality of Republic of Indonesia, post-reformation of leadership in Indonesia occurred drastically changing in leadership. It’s become a policy of country in freedom autonomy local for managing, own regional, with various implementation model of society empowerment toward Indonesia independently and prosperity. That is inserted in Indonesia nationality at constitution of regional autonomy No. 32, 2004, that vision to be aspiration of 5th namely toward justice for all Indonesia society. Thus, for obtain society vision justice and properity, needed the leadership model of Triple Helix in implementation of society empowerment, because that is become a new breakthrough to integrated elite group in conducting leadership in locally democratic era toward welfare. Leadership implementation of triple helix is a model of integrated of leadership thought in development of society empowerment independent and toward welfare, this integration is between government, academician, bussinessman to be one vision in context of development of society empowerment based on innovative, independent, toward welfare of local society in Indonesia Keywords: Recontruction, leadership, empowerment, society, autonomy